(untitled) (Bangladesh Journal of Animal Science, 2012)
The survey was carried out in villages of two upazilas under Satkhira district covering 100 members and 50 non-members of field fertility clinics (FFC) during January to March 2009. Evidence showed that socioeconomic characteristics were more or less same in both farms. The study revealed that annual average milk production per farm for two categories of farmers were 7215.87 litres and 5206.52 litres respectively. Annual milk production per farm of member farmers was higher by 1973.21 litres over that of non-member farmers. Net returns per farm were Tk. 175670.30 and Tk. 67611.51 for member and non-member farmers respectively. Benefit cost ratio for community member farmers were 1.80, for non-members were 1.62 and for all categories of farmers were 1.74 indicating that dairy farming was profitable. However, member farmers made more profit than non-member farmers through dairy farming. The study concluded that proper steps could be taken to make the dairy farming as a viable commercial enterprise. Therefore, the FFC should extend more services, which will encourage expansion of dairy farming and thereby, will contribute to increase of milk production in the area and in the country as a whole. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9925 BJAS 2009; 38(1-2): 164-169